PERBEDAAN SKOR WORK ENGAGEMENT GURU SMP NEGERI DI KECAMATAN DENPASAR UTARA PADA KELOMPOK MASA KERJA 1-4 TAHUN, 5-19 TAHUN, DAN LEBIH DARI 20 TAHUN - Indraswari, Putu Gita; Adiputra, I Nyoman (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic); Vol 1 No 2 (2015): Volume 1 No 2 Desember 2015DO - 10.24843/JEI.2015.v01.i02.p04)
Work engagement is influenced by job demand, job resources, and personal resources. However, there are differences in the results of previous studies on the relationship oflength of service with work engagement. This study aims to prove the difference ofwork engagement score on junior high school teachers in North Denpasar with 1-4 year,5-19 year, and more than 20 year length of service.  It has been  implemented anobservational study with cross-sectional design, conducted at the Junior High School, 38located in North Denpasar District, include SMPN 2 Denpasar, SMPN 3 Denpasar, SMPN 4 Denpasar, SMPN 5 Denpasar, SMPN 10 Denpasar, and SMPN 12 Denpasar. Total subjects were used in this study were 147 people. Work engagement scores were calculated using Utretch Work Engagement Scale (UWES). The length of service is classified into 1-4 years, 5-19 years, and more than 20 years. Total Work EngagementScores were compared using Kruskal-Wallis test with a significance level of 0.05. Showed that there was an increase in mean scores significantly in group 1-4 yearslength of service with a mean of 79.66 ± 12.98 and group over 20 years with a mean score of 87.01 ± 7.99 (p <0.05 ). A significant result was also obtained in the group of5-19-year length of service with mean score 80.84 ± 8.75 and group with over 20 years with  a mean score of  87.01  ±  7.99.  However,  based on the  correlation  test, the association  between  engagement and length of service is not  a significant.  It was concluded that there was difference in mean scores significantly in group work periodof 1-4 years and group over 20 and also group of 5-19-year length of service with and group with over 20 years. So that should be efforts to improve work engagement in the group of teachers with of 1-4 years and 5-19 years length of service
Keywords: length of service, teacher, work engagement